Political mobility of Chinese regional leaders : performance, preference, promotion - Qiao, Liang (Assistant professor of political science) (Milton Park, Abingdon, Oxon ; New York, NY : Routledge, Taylor & Francis Group, 2017)
A monarch is usually born, a member of parliament or a president is usually elected, but a regional leader in China is usually orchestrated to replace his or her predecessor through an opaque process and for reasons not normally made public. The professional trajectories of Chinese regional leaders are mysterious in many ways. Their promotions and demotions can be "predictable" in terms of their age, gender, nationality, education, factions, and previous engagements in the political system. Yet, speaking of their capability, performance, opportunities and arrangements, their future can also be "unexpected". Such arrangements are always originated from the Organization (zuzhi) which represents the Chinese Communist Party. What are the factors the organization considers in order to make its final decisions on nominating and appointing a regional leader?Today's regional leaders of China will very likely become the central leaders of China in the future. By making an empirical analysis of Chinese regional leaders' political mobility, Qiao establishes a descriptive political mobility model that reveals leadership trajectories in Chinese politics.
Conclusion: Chinese political elites "on the go"6 For the harmonious society: downgraded and demoted regional leaders; Downward political mobility analysis of regional leaders in the post-Deng Xiaoping era; Geopolitical preferences and regional leaders' political resilience; Conclusion: the regime's configuration of regional leaders' political mobility; 7 Conclusions; The people: judging the regime by its elites; The elites: between the regime and the people; The regime: ruling the people with the elites; Selected bibliography; Index.
Includes bibliographical references and index.
Print version record.
Added to collection customer.56279.3
Keywords: Local officials and employees -- Selection and appointment -- China; Local government -- China; China -- Administrative and political divisions; Fonctionnaires locaux -- Sélection et nomination -- Chine; Administration locale -- Chine; Chine -- Divisions politiques et administratives; POLITICAL SCIENCE -- General; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Administrative and political divisions; Local government; Local officials and employees -- Selection and appointment; China